Bibliometric and Systematic Literature Review : Kemampuan Berpikir Kritis dalam Konteks Penanganan Perubahan Iklim (SDGs 13) pada Pembelajaran Biologi: (A Bibliometric and Systematic Literature Review of Critical Thinking Skills in the Context of Climate Change Action (SDG 13) in Biology Education) - Maharani, Salsabilla; Kusnadi , Kusnadi; Nurjhani Kusumastuti, Mimin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Integrating critical thinking in biology education is increasingly urgent to strengthen environmental awareness and support climate action aligned with SDG 13. This study investigates research trends on the relationship between critical thinking skills and environmental awareness within biology education in the context of climate change action. A bibliometric and literature review approach was applied to journal articles indexed in Scopus and Google Scholar. Data were collected using Publish or Perish 8 and analyzed through five phases: data collection, keyword identification, relationship-matrix construction, visualization, and interpretation. Bibliometric mapping was performed using VOSviewer. Publications from 2020–2025 show dominant themes including critical thinking, problem solving, climate change, climate action, sustainability, and education for sustainable development (ESD). The mapping indicates biology education as a major domain connecting critical thinking, environmental awareness, and climate action research related to SDG 13. The findings provide an overview of recent research directions and identify key thematic clusters that can inform future development of biology learning models to support climate action through strengthened critical thinking and environmental awareness. Abstrak. Integrasi kemampuan berpikir kritis dalam pembelajaran biologi semakin mendesak untuk memperkuat kesadaran lingkungan dan mendukung aksi iklim sesuai SDGs 13. Penelitian ini menelaah tren riset mengenai keterkaitan kemampuan berpikir kritis dan kesadaran lingkungan dalam konteks pendidikan biologi yang berorientasi pada aksi perubahan iklim. Penelitian menggunakan pendekatan tinjauan literatur dan analisis bibliometrik terhadap artikel jurnal terindeks Scopus dan Google Scholar. Pengambilan data dilakukan dengan Publish or Perish 8, kemudian dianalisis melalui lima tahap yakni pengumpulan data, identifikasi kata kunci, penyusunan matriks keterkaitan, visualisasi, serta interpretasi. Pemetaan bibliometrik dilakukan menggunakan VOSviewer. Publikasi periode 2020–2025 didominasi tema berpikir kritis, pemecahan masalah, perubahan iklim, aksi iklim, keberlanjutan, dan education for sustainable development (ESD). Pemetaan menunjukkan pendidikan biologi sebagai domain utama yang menghubungkan riset berpikir kritis, kesadaran lingkungan, dan aksi iklim terkait SDGs 13. Temuan memberikan gambaran arah riset terkini dan klaster tema utama yang dapat menjadi dasar pengembangan model pembelajaran biologi untuk mendukung aksi iklim melalui penguatan berpikir kritis dan kesadaran lingkungan.